Cationic photocuring adhesive and preparation method thereof

By using cationic photocuring adhesives, combined with cationic photoinitiator, thickening trigger and coupling agent, the problems of insufficient adhesive force and oxygen polymerization resistance in the prior art are solved, stronger adhesive force and faster reaction speed are achieved, production costs are reduced, and the adhesive force continues to increase after bonding to become a battery string.

CN119614116APending Publication Date: 2025-03-14CANNNOVATION LOW CARBON NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714659.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the free radical acrylic photocuring adhesive has a great impact on oxygen polymerization in the presence of oxygen, resulting in a hindered adhesive performance and insufficient adhesion. In addition, the main gate-free component is prone to falling off the welding tape and the battery sheet during production, handling or use.

Method used

The cationic photocuring adhesive is used to increase the adhesive force by increasing the cationic photoinitiator, thickening trigger and coupling agent, and enhance the adhesive performance through the post-curing effect of the cation.

Benefits of technology

It achieves stronger bonding force, can resist oxygen convergence in the air atmosphere, has a faster reaction speed, ensures adhesion, while reducing the number of glue points, saves production costs, and continuously improves after bonding to become a battery string.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614116A_ABST
    Figure CN119614116A_ABST
Patent Text Reader

Abstract

The invention provides a cationic photocuring adhesive and a preparation method thereof, and relates to the technical field of adhesive preparation, the cationic photocuring adhesive comprises 65-90% of matrix resin, 5-30% of an active diluent, 1-5% of a cationic photoinitiator, 0.5-3% of a thickening trigger, and 1-2% of a coupling agent; the preparation method of the adhesive comprises the following steps: respectively weighing the components according to the mass percent; putting the weighed raw materials into a planetary stirrer for stirring to obtain a stirred product; and sequentially carrying out vacuum defoaming and filtering on the stirred product to obtain the cationic photocuring adhesive. The technical problems that in the prior art, due to the fact that the oxygen inhibition influence of an adhesive is large, the bonding force is insufficient, and a welding strip and a battery piece fall off are solved, and the better curing effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesive preparation, in particular to a cationic photocuring adhesive and a preparation method thereof, and also to a battery string obtained by bonding a welding strip and a plurality of main grid-free battery cells using the cationic photocuring adhesive. Background Art

[0002] In the current solar module manufacturing process, photovoltaic ribbons, usually made of metal materials, are used to connect solar cells to form a current loop. They have excellent electrical conductivity and can reduce the resistance of the cells, thereby improving the power generation efficiency of the panels. Photovoltaic ribbons are usually connected to cells by bonding, because bonding technology can improve the bonding strength between the two, prevent the ribbons from detaching from the cells during transportation, and simplify the module manufacturing process.

[0003] In the prior art, free radical acrylic light-curing adhesives are used to bond photovoltaic ribbons to cells. This bonding method has the advantage of fast curing speed and can meet the requirements of rapid production to a certain extent.

[0004] However, due to the presence of oxygen, the oxygen inhibition effect of free radical acrylic light-curing adhesive becomes greater, the bonding performance is hindered, and the bonding strength is insufficient. This insufficient bonding strength not only increases the amount of glue used, but also increases the demand for light energy. In addition, due to insufficient bonding strength, the main grid-free module is prone to the phenomenon of the soldering ribbon and the battery cell falling off during production, transportation or use. Summary of the invention

[0005] The purpose of the present invention is to provide a cationic photocurable adhesive to alleviate the technical problem in the prior art that the oxygen inhibition effect of the adhesive becomes greater, resulting in insufficient adhesion and the detachment of the soldering tape and the battery cell.

[0006] Another object of the present invention is to provide a method for preparing a cationic light-curing adhesive.

[0007] Another object of the present invention is to provide a battery string obtained by bonding a welding strip and a plurality of busbar-free battery cells using a cationic photocuring adhesive.

[0008] To achieve the above objectives, the technical solution of this application is as follows:

[0009] The invention provides a cationic light-curing adhesive, which is composed of the following components in percentage by mass: 65% to 90% of a base resin, 5% to 30% of a reactive diluent, 1% to 5% of a cationic light initiator, 0.5% to 3% of a thickening trigger, and 1% to 2% of a coupling agent.

[0010] Further, the base resin includes at least one of aliphatic modified epoxy resin, bisphenol A epoxy resin, polyurethane modified epoxy resin, silicone modified epoxy resin or alicyclic epoxy resin.

[0011] Further, the active diluent includes one of 3-hydroxymethyl-3-ethyloxetane, 3-benzyloxymethyl-3-ethyloxetane, 3,3'-[oxybismethylene]bis[3-ethyl]oxetane or 3-ethyl-3-[(oxyethylene-2-methoxy)methyl]oxetane.

[0012] Further, the cationic photoinitiator includes at least one of diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis[4-diphenylsulfoniumphenyl]sulfide dihexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate or bis(4-tert-butylphenyl)iodonium hexafluorophosphate.

[0013] Furthermore, the thickening trigger includes at least one of an organic bentonite thickener, a castor oil thickener, a polyurea thickener, a silica thickener or a sodium polyamide thickener.

[0014] Further, the coupling agent includes at least one of silane coupling agent KH-550, silane coupling agent KH-560, phosphate-modified epoxy coupling agent or titanate epoxy coupling agent.

[0015] The present invention also provides a method for preparing a cationic light-curing adhesive, comprising the following steps:

[0016] Step 1, weigh the following components respectively according to mass percentage: 65% to 90% of base resin, 5% to 30% of active diluent, 1% to 5% of cationic photoinitiator, 0.5% to 3% of thickening trigger, and 1% to 2% of coupling agent to obtain the weighed raw materials;

[0017] Step 2, putting the weighed raw materials into a planetary mixer for stirring to obtain a stirred product;

[0018] Step 3: vacuum degassing and filtering the stirred product in turn to obtain a cationic UV-curing adhesive.

[0019] Furthermore, the stirring temperature in step 2 is 24° C. to 26° C., and the stirring time is 10 min to 20 min.

[0020] Furthermore, step 3 is specifically implemented according to the following steps:

[0021] Step 3.1, vacuum degassing the stirred product to a vacuum degree of less than or equal to -0.09 MPa, with an extraction time of 30 min to 40 min to obtain an intermediate product;

[0022] Step 3.2: sieve the intermediate product using filter cloth with a mesh size of 200 to 300 to obtain a cationic light-curing adhesive.

[0023] The present invention also provides a battery string, which uses a cationic light-curing adhesive to adhere a welding strip and a plurality of main-grid-free battery sheets.

[0024] Beneficial effects of the present invention:

[0025] The cationic photocuring adhesive of the present invention is made to have stronger bonding strength by adding cationic photoinitiators, thickening triggers and coupling agents. At the same time, cations have lower energy requirements during curing, can better resist oxygen inhibition brought by the air atmosphere, and have a faster reaction speed. When the cationic photocuring adhesive of the present invention is used to bond battery strings, it can ensure adhesion while reducing the number of glue points and saving production costs. In addition, due to the unique post-curing effect of cations, the bonding strength between the glue points of the main grid-free battery sheet and the solder strip will continue to increase after bonding into a battery string.

[0026] The preparation method of the cationic light-curing adhesive of the present invention is simple, the process flow operation is not complicated, and it can be used for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 A flow chart of a method for preparing a cationic light-curing adhesive provided by an embodiment of the present invention;

[0029] Figure 2 A diagram showing the locations of glue points of a cationic light-curing adhesive in a battery string according to an embodiment of the present invention.

[0030] Figure numerals: 100 - glue point; 200 - battery cell; 300 - welding wire. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0032] In a first aspect, the present invention provides a cationic photocurable adhesive, which is composed of the following components in mass percentage: 65% to 90% of a base resin, 5% to 30% of an active diluent, 1% to 5% of a cationic photoinitiator, and 0.5% to 3% of a thickening trigger and a coupling agent.

[0033] In the embodiment of the present invention, the base resin may be, but is not limited to, 65%, 70%, 80% or 90% by mass percentage;

[0034] In terms of mass percentage, the active diluent may be, but is not limited to, 5%, 6%, 15%, 21% or 30%;

[0035] In terms of mass percentage, the cationic photoinitiator may be, but is not limited to, 1%, 2%, 3% or 5%;

[0036] In terms of mass percentage, the thickening trigger may be, but is not limited to, 0.5%, 1%, 1.5% or 3%;

[0037] In terms of mass percentage, the coupling agent may be, but is not limited to, 1%, 1.5% or 2%.

[0038] It should be noted that the matrix resin accounts for 65% to 90% of the total formula and serves as a matrix. Through its adhesiveness, it firmly combines the battery cells and welding wires together to ensure the integrity and functionality of the composite material.

[0039] It should be noted that the 5% to 30% active diluent is a low molecular weight resin used to reduce the viscosity of the base resin, improve fluidity and coating properties, and does not affect the final performance after curing.

[0040] It should be noted that 1% to 5% of cationic photoinitiators decompose under the action of light to produce free radicals, which trigger the polymerization reaction of the resin, can affect the curing speed and improve the curing efficiency of the photocurable material. Cationic photoinitiators can reduce the energy required for curing, are not affected by oxygen inhibition, increase the adhesion between the welding wire and the battery cell, reduce the amount of glue used, and reduce costs. At the same time, the unique post-curing effect of cationic photoinitiators makes the adhesion between the glue points of the battery cell and the welding ribbon continue to increase after the battery string is formed.

[0041] It should be noted that 0.5% to 3% of the thickening trigger is used to control the viscosity of the adhesive, prevent the glue from sagging, and ensure that the rheological properties of the adhesive meet the application requirements under specific conditions (temperature, pH value changes).

[0042] It should be noted that 1% to 2% coupling agent: The coupling agent is used to improve the bonding performance between the battery cell and the solder strip. Due to the different surface properties between the two, the coupling agent can increase the bonding strength and reduce the number of bonding points.

[0043] In an embodiment of the present invention, the base resin includes one or more of aliphatic modified epoxy resin, bisphenol A epoxy resin, polyurethane modified epoxy resin, silicone modified epoxy resin or alicyclic epoxy resin. For example, it can be aliphatic modified epoxy resin and bisphenol A epoxy resin, polyurethane modified epoxy resin and alicyclic epoxy resin, silicone modified epoxy resin and alicyclic epoxy resin, or any one of the above can be used alone.

[0044] In an embodiment of the present invention, the active diluent includes one of 3-hydroxymethyl-3-ethyloxetane, 3-benzyloxymethyl-3-ethyloxetane, 3,3'-[oxybismethylene]bis[3-ethyl]oxetane or 3-ethyl-3-[(oxyethylene-2-methoxy)methyl]oxetane. For example, it can be 3-hydroxymethyl-3-ethyloxetane, 3-benzyloxymethyl-3-ethyloxetane, 3,3'-[oxybismethylene]bis[3-ethyl]oxetane, or 3-ethyl-3-[(oxyethylene-2-methoxy)methyl]oxetane.

[0045] In an embodiment of the present invention, the cationic photoinitiator includes one or more of diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis[4-diphenylsulfonium phenyl]sulfide dihexafluoroantimonate, 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate or bis(4-tert-butylbenzene)iodonium hexafluorophosphate. For example, it may be diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis[4-diphenylsulfonium phenyl]sulfide dihexafluoroantimonate, 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate, bis(4-tert-butylbenzene)iodonium hexafluorophosphate, or a mixture of the above.

[0046] In an embodiment of the present invention, the thickening trigger includes one or more of an organic bentonite thickener, a castor oil thickener, a polyurea thickener, a silica thickener, or a sodium polyamide thickener. For example, it can be an organic bentonite thickener, a castor oil thickener, a polyurea thickener, a silica thickener, a sodium polyamide thickener, or a mixture of the above.

[0047] In an embodiment of the present invention, the coupling agent includes one or more of silane coupling agent KH-550, silane coupling agent KH-560, phosphate-modified epoxy coupling agent or titanate epoxy coupling agent. For example, it can be coupling agent KH-550, silane coupling agent KH-560, phosphate-modified epoxy coupling agent, titanate epoxy coupling agent, or a mixture of the above.

[0048] Second, as Figure 1 As shown, the present invention provides a method for preparing a cationic light-curing adhesive, which comprises the following steps:

[0049] Step 1, weigh the following components respectively according to mass percentage: 65% to 90% of base resin, 5% to 30% of active diluent, 1% to 5% of cationic photoinitiator, 0.5% to 3% of thickening trigger, and 1% to 2% of coupling agent to obtain the weighed raw materials;

[0050] Step 2: Put the weighed raw materials into a planetary mixer and stir them at a temperature of 24°C to 26°C for 10 to 20 minutes to obtain a stirred product;

[0051] Step 3: vacuum degassing and filtering the stirred product in turn to obtain a cationic light-curing adhesive.

[0052] Step 3.1, vacuum degassing the stirred product to a vacuum degree of less than or equal to -0.09 MPa, with an extraction time of 30 min to 40 min to obtain an intermediate product;

[0053] Step 3.2: sieve the intermediate product using filter cloth with a mesh size of 200 to 300 to obtain a cationic light-curing adhesive.

[0054] The preparation method of the present invention is easy to operate and has strong practicality; the prepared adhesive can reduce energy demand, save electricity costs, and improve production efficiency. In addition, the adhesive has stronger bonding strength, reduces the number of glue points, and saves production costs.

[0055] like Figure 2 As shown, the present invention also provides a battery string obtained by bonding a welding strip and a plurality of busbar-free battery cells using a cationic light-curing adhesive. There are two bonding glue points 100 between each battery cell 200 and the welding wire 300.

[0056] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0057] Example 1

[0058] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 80% of a base resin (40% of aliphatic modified epoxy resin and 40% of bisphenol A epoxy resin), 15% of 3-hydroxymethyl-3-ethyloxetane, 3% of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, 1% of a silica thickener and 1% of a silane coupling agent KH-550.

[0059] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 24° C. for 10 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 30 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 200 to obtain the adhesive of this embodiment.

[0060] Example 2

[0061] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 70% of a base resin (50% of a polyurethane-modified epoxy resin and 20% of an alicyclic epoxy resin), 21% of 3-benzyloxymethyl-3-ethyloxetane, 5% of 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, 3% of a sodium polyamide thickener, and 1% of a phosphate-modified epoxy coupling agent.

[0062] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 25° C. for 15 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 20 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 250 to obtain the adhesive of this embodiment.

[0063] Example 3

[0064] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 90% of a base resin (50% of a silicone epoxy resin and 20% of an alicyclic epoxy resin), 6% of 3-benzyloxymethyl-3-ethyloxetane, 2% of 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, 1% of a sodium polyamide thickener, and 1% of a phosphate-modified epoxy coupling agent.

[0065] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 26° C. for 20 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 40 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh size of 300 to obtain the adhesive of this embodiment.

[0066] Example 4

[0067] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 65% of silicone epoxy resin, 30% of 3,3'-[oxybismethylene]bis[3-ethyl]oxetane, 1% of bis[4-diphenylsulfoniumphenyl]sulfide dihexafluoroantimonate, 3% of organic bentonite thickener and 1% of silane coupling agent KH-560.

[0068] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 24° C. for 14 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 32 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 250 to obtain the adhesive of this embodiment.

[0069] Example 5

[0070] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 90% of silicone epoxy resin (50% of silicone-modified epoxy resin and 40% of alicyclic epoxy resin), 5% of 3-ethyl-3-[(ethylene oxide-2-methoxy)methyl]oxetane, 2% of 3-ethyl-3-[(ethylene oxide-2-methoxy)methyl]oxetane, 0.5% of castor oil thickener and 2.5% of titanate epoxy coupling agent.

[0071] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 24° C. for 19 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 38 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 300 to obtain the adhesive of this embodiment.

[0072] Example 6

[0073] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 90% of silicone epoxy resin (40% of bisphenol A epoxy resin and 50% of alicyclic epoxy resin), 6% of 3-hydroxymethyl-3-ethyloxetane, 1% of 4-(phenylthio)phenyl diphenylsulfonium hexafluorophosphate, 1.5% of polyurea thickener and 1.5% of titanate epoxy coupling agent.

[0074] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 25° C. for 20 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 40 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 300 to obtain the adhesive of this embodiment.

[0075] Example 7

[0076] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 80% of silicone epoxy resin (20% of alicyclic epoxy resin and 60% of polyurethane modified epoxy resin), 15% of 3,3'-[oxybismethylene]bis[3-ethyl]oxetane, 2% of bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate, 1% of silica thickener and 2% of silane coupling agent KH-550.

[0077] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 24° C. for 15 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 39 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 200 to obtain the adhesive of this embodiment.

[0078] Example 8

[0079] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 70% of aliphatic modified epoxy resin, 20% of 3-hydroxymethyl-3-ethyloxetane, 5% of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, 3% of organic bentonite thickener and 2% of titanate epoxy coupling agent.

[0080] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 25° C. for 13 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 39 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh size of 300 to obtain the adhesive of this embodiment.

[0081] Example 9

[0082] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 80% of silicone epoxy resin (20% of alicyclic epoxy resin and 60% of silicone-modified epoxy resin), 15% of 3-ethyl-3-[(ethylene oxide-2-methoxy)methyl]oxetane, 1% of bis(4-tert-butylbenzene)iodonium hexafluorophosphate, 3% of organic bentonite thickener and 1% of silane coupling agent KH-560.

[0083] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 25° C. for 17 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 32 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 200 to obtain the adhesive of this embodiment.

[0084] Example 10

[0085] The present embodiment provides an adhesive, which is prepared according to the following mass percentages: 90% of silicone epoxy resin (20% of aliphatic modified epoxy resin and 70% of silicone modified epoxy resin), 5% of 3,3'-[oxybismethylene]bis[3-ethyl]oxetane, 2% of diphenyl-(4-phenylthio)phenylsulfonium hexafluoroantimonate, 1.5% of silica thickener and 1.5% of phosphate modified epoxy coupling agent.

[0086] The preparation method of the adhesive of this embodiment comprises: weighing the above components according to percentage and putting them into a planetary mixer for stirring at a stirring temperature of 26° C. for 17 minutes to obtain a stirred product; vacuum degassing the stirred product to make the vacuum degree less than or equal to -0.09 MPa for 35 minutes to obtain an intermediate product; sieving the intermediate product with a filter cloth with a mesh number of 300 to obtain the adhesive of this embodiment.

[0087] Comparative Example 1

[0088] Comparative Example 1 provides an adhesive, which is obtained by mixing according to the following mass percentages: 80% acrylic free radical prepolymer, 15% acrylic UV monomer, 3% photoinitiator, and 2% auxiliary agent.

[0089] The cationic photocurable adhesives obtained in Examples 1-10 and Comparative Example 1 were tested in terms of curing time, bonding strength, bonding strength after 6 hours, and the number of glue points of a 210 mm single welding wire. The results are shown in Table 1.

[0090] Table 1

[0091]

[0092]

[0093] From the data in Table 1, it can be seen that the adhesives of Examples 1-10 of the present invention have good bonding strength for the bonding of welding wires to non-busbars. The curing time of Examples 1-10 of the present invention is shorter than that of Comparative Example 1, and the post-curing effect of the cations can continuously improve the bonding strength after forming a battery string; the bonding strength just after application and the bonding strength after 6 hours are better than Comparative Example 1. The use of coupling agents can improve the bonding strength to metals, reduce the number of glue points from 4 to 2, and reduce costs.

[0094] Finally, it should be noted that the specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A cationic light-curing adhesive, characterized in that: The composition is composed of the following components in terms of mass percentage: 65% to 90% of base resin, 5% to 30% of active diluent, 1% to 5% of cationic photoinitiator, 0.5% to 3% of thickening trigger, and 1% to 2% of coupling agent.

2. The cationic light-curing adhesive according to claim 1, characterized in that: The base resin includes at least one of aliphatic modified epoxy resin, bisphenol A epoxy resin, polyurethane modified epoxy resin, silicone modified epoxy resin or alicyclic epoxy resin.

3. The cationic light-curing adhesive according to claim 2, characterized in that: The active diluent includes one of 3-hydroxymethyl-3-ethyloxetane, 3-benzyloxymethyl-3-ethyloxetane, 3,3'-[oxybismethylene]bis[3-ethyl]oxetane or 3-ethyl-3-[(oxyethylene-2-methoxy)methyl]oxetane.

4. The cationic light-curing adhesive according to claim 3, characterized in that: The cationic photoinitiator includes at least one of diphenyl-(4-phenylsulfonium)phenylsulfonium hexafluoroantimonate, bis[4-diphenylsulfoniumphenyl]sulfide dihexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide-bishexafluorophosphate or bis(4-tert-butylphenyl)iodonium hexafluorophosphate.

5. The cationic light-curing adhesive according to claim 4, characterized in that: The thickening trigger includes at least one of an organic bentonite thickener, a castor oil thickener, a polyurea thickener, a silicon dioxide thickener or a sodium polyamide thickener.

6. The cationic light-curing adhesive according to claim 5, characterized in that: The coupling agent includes at least one of silane coupling agent KH-550, silane coupling agent KH-560, phosphate-modified epoxy coupling agent or titanate epoxy coupling agent.

7. A battery string, characterized in that: The cationic photocurable adhesive according to any one of claims 1 to 6 is used to bond the soldering tape and a plurality of main grid-free solar cells.

8. A method for preparing a cationic light-curing adhesive, for preparing the cationic light-curing adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, weigh the following components respectively according to mass percentage: 65% to 90% of base resin, 5% to 30% of active diluent, 1% to 5% of cationic photoinitiator, 0.5% to 3% of thickening trigger, and 1% to 2% of coupling agent to obtain the weighed raw materials; Step 2, putting the weighed raw materials into a planetary mixer for stirring to obtain a stirred product; Step 3: vacuum degassing and filtering the stirred product in turn to obtain a cationic light-curing adhesive.

9. The method for preparing a cationic light-curing adhesive according to claim 8, characterized in that: The stirring temperature in step 2 is 24° C. to 26° C., and the stirring time is 10 min to 20 min.

10. The method for preparing a cationic light-curing adhesive according to claim 8, characterized in that: The step 3 is specifically implemented according to the following steps: Step 3.1, vacuum degassing the stirred product to a vacuum degree of less than or equal to -0.09 MPa, with an extraction time of 30 min to 40 min to obtain an intermediate product; Step 3.2: sieve the intermediate product using filter cloth with a mesh size of 200 to 300 to obtain a cationic light-curing adhesive.